INFORMATIVENESS OF THE GPR METHOD ON THE EXAMPLE OF RESULTS FROM EXPERIMENTAL SITE - Chernov, A.; Reva, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this article the results of Ground penetrating radar (GPR) surveys on experimental site near Institute of Geology of Taras Shevchenko National University of Kyiv (Kyiv, Ukraine) are represented. GPR method has been developed since 1970, but the problem of GPR profiles quality assessment and the best settings for GPR surveys remains controversial. GPR researches on artificially created site were carried out by three radars with 300 MHz and 500 MHz antennas. Assessment of GPR method informativeness was performed according to the analysis of experimental data with the following criteria: correspondence of registered anomalies on GPR profiles to the actual location of the objects; dependence of GPR profiles quality on the central frequency of antenna, step of measurement, settings of survey depth, season of surveying and number of points on vertical scale. Comparative analysis of the GPR investigations quality was carried out with method developed by authors. As a result of experimental data analysis conclusions and practical recommendations, which can be applied for GPR investigations on the territories, with similar geological structure and similar characteristics of objects to experimental site, are pointed out.
Keywords: ground penetrating radar; GPR; GPR profile; dielectric permittivity; electrical resistivity; GPR survey settings; pipes; metal; loam; sand; gravel; void